2021
DOI: 10.1021/acsomega.1c04528
|View full text |Cite
|
Sign up to set email alerts
|

PdII on Guanidine-Functionalized Fe3O4 Nanoparticles as an Efficient Heterogeneous Catalyst for Suzuki–Miyaura Cross-Coupling and Reduction of Nitroarenes in Aqueous Media

Abstract: This paper presents guanidine-functionalized Fe 3 O 4 magnetic nanoparticle-supported palladium (II) (Fe 3 O 4 @Guanidine-Pd) as an effective catalyst for Suzuki–Miyaura cross-coupling of aryl halides using phenylboronic acids and also for selective reduction of nitroarenes to their corresponding amines. Fe 3 O 4 @Guanidine-Pd synthesized is well characterized using FT-IR sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 65 publications
0
23
0
Order By: Relevance
“…From the TEM micrographs, the nano-catalysts are agglomerated into spherical shapes. This tendency is not surprising, given the nanoparticles’ small size and magnetic properties [ 24 ]. The appearance of dark shades in the images (b–e) implies that the electron beam did not penetrate the sample, which could be a result of the homogeneous phase of the catalyst that is attached to the support occluding the electron beam.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the TEM micrographs, the nano-catalysts are agglomerated into spherical shapes. This tendency is not surprising, given the nanoparticles’ small size and magnetic properties [ 24 ]. The appearance of dark shades in the images (b–e) implies that the electron beam did not penetrate the sample, which could be a result of the homogeneous phase of the catalyst that is attached to the support occluding the electron beam.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 5 a shows the overview spectra of the composition of the catalyst Fe 2 O 3 @C2 with atomic percentage, whereas the analysis for the elements Fe, Cl, Si are shown in Figure 5 c–e. We can fit the N 1s spectrum, Figure 5 b, into a typical peak corresponding to a metal-N species (399.1 eV); these species in Ni-N-C support the dispersion of Ni in the form of Ni-N coordination [ 1 , 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…SEM images of the catalyst after the second run revealed the agglomeration of Pd nanoparticles on the surface of the catalyst, which is the major reason for the drop in the product yields as shown in Figure 8. The yield after the second run reaction was still high (>90%) and dropped to 80% after the fifth run but dramatically decreased to 50% after the sixth 1 a CS-NNSB-Pd(II) (0.006) -50 c 0.08 97 Baran [28] 2 ImmPd-MNPs (0.14) TBAB/H 2 O r.t. 0.3 93 Hajipour and Tavangar-Rizi [29] 3 CS-Biguanidine/Pd (0.15) EtOH/H 2 O 40 1 98 Veisi et al [32] 4 Pd@Cell-EDTA (0.05) EtOH/H 2 O 78 0.5 96 Xu et al [11] 5 PdNPs@chitosan (0.1) TBAB 90 5 97 Cotugno et al [17] 6 PdNPs/GO-TETA (0.01) DMF/H 2 O 90 0.4 98 Mirza-Aghayan et al [19] 7 F e 3 O 4 @SiO 2 /PropylSB@Pd (0.1) H 2 O/EtOH 80 c 0.5 92 Hasan et al [6] 8 F e 3 O 4 /CS-Me@Pd (0.003) EtOH/H 2 O 50 30 98 Wang et al [36] 9 Cell-Sc-Pd(II) (0.002) EtOH/H 2 O 70 1.5 74 Pharande et al [12] 10 Fe 3 O 4 -CS@tet-Pd(II) EtOH/H 2 O 90 2.2 91 Nasrollahzadeh et al [40] 11 a Fe 3 O 4 @Guanidine-Pd (0.22) H 2 O 70 0.5 90 Halligudra et al [8] 12 Fe 3 O 4 @SiO 2 -TCT-GA-Pd(0) (0.12) EtOH/H 2 O 50 1.5 95 Eslahi et al [9] 13 PdNPs@CS/δ-FeOOH (0.05) EtOH/H 2 O r.t. 3 91 Çalıs ¸kan and Baran [21] 14 Fe 3 O 4 @MCM41@NHC@Pd (0.01) run. From these results, it can be concluded that the catalyst was effective for five runs.…”
Section: Recycle Of the Catalystmentioning
confidence: 99%
“…[1][2][3] Among the crosscoupling reactions, the Suzuki-Miyaura reaction is one of the powerful tools to create a carbon-carbon bond from the cross-coupling of aryl boronic acid and aryl halides using a palladium catalyst to synthesize biaryls for industrial uses related to pharmaceuticals, agrochemicals, polymers, and materials. [4,5] Recently, many research groups have demonstrated the use of various kinds of materials as catalyst support for the Suzuki-Miyaura reaction, including organic and inorganic compounds such as metal oxides, [6][7][8][9][10] polymers, [11][12][13][14][15][16][17][18] carbon materials, [19,20] and composite materials. [21,22] Among these support materials, natural polymers have attracted much attention due to their availability, nontoxicity, biodegradability, and low cost.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation